CRITICAL LEADERSHIP TRAITS FOR SUCCESSFUL LARGE-SCALE AGILE TRANSFORMATION IN FINANCIAL INSTITUTIONS (Interdisciplinary Studies Journal, 2026)
This study analyzes the leadership characteristics that effectively influence large-scale agile transformation in a public financial institution, highlighting the need to adapt leadership styles in the face of agile challenges. The article addresses the influence of leadership practices on agile transformation in the financial sector, offering new insights into the adaptation of leadership styles that foster an agile culture. It contributes to the practical understanding of how leaders can promote innovation and efficiency in changing contexts. Using a quantitative approach with 211 leaders, the study employed a survey and Exploratory Factor Analysis (EFA) to redefine and identify leadership characteristics critical to agile transformation. The results indicate that adaptive and empowering leadership characteristics are vital during agile transformations, with leaders promoting autonomy, continuous learning, and rapid adaptation. This work enriches leadership theory in agile contexts and highlights the usefulness of EFA for refining leadership characteristics in applied research. The practical implications help organizations shape their leadership development strategies, supporting organizational agility and sustainable change. These are essential for leaders aiming for effectiveness in dynamic environments.
Keywords: Agile Leadership; Large-Scale Agile Transformation; Agile Methodology; Organizational Culture